Locking small solvents by hypercrosslinked polymers towards sterically hindered organogels - Bin Zhang; Guoliang Zhang; Guangzhao Zhang; Chunfeng Ma (Nature Communications)
Abstract Sterically hindered organogels are promising as coatings, adhesives and structural materials since they can overcome the low strength and poor stability of traditional gel materials. However, limited by the mesh size of the polymer network, it is a significant challenge to entrap small solvents to preparing sterically hindered organogels. Herein, a hypercrosslinked polyurea network with small mesh size (~1.17 nm) is designed for capturing small-sized bio-based acetyl tributyl citrate molecules (~1.25 nm). The rational combination makes the system demonstrate low viscosity, high wettability, strong permeation, and fast curing. They can instantly form mechanically robust polyurea organogels with environmental adaptability to various temperatures and water conditions, and stability against high pressures, high temperatures, and solvent immersion. Owing to these properties, the polyurea organogels show application prospects as a permeable coating for rusty steel, a strong adhesive to repair concrete, and reinforcement structural materials to manufacture low-carbon concrete.